Taxonomy of functional and dysfunctional conflicts in animation film Elemental (2023) - Jodi Ferdianto Panjaitan; Merry Rullyanti; Lina Tri Astuty Beru Sembiring (Universitas Pakuan, 2025)
This research was conducted to describe the functional and dysfunctional conflicts faced by the main characters and how the conflict is managed in the Elemental movie. The Elemental movie as a data source is analyzed using two theories related to the topic that has been taken, namely the conflict theory by Madiha Shazia (2015) and the conflict management theory by Mouton Blake. This study used a descriptive qualitative method. Data is taken in the form of dialogue and to identify the types of conflict and types of conflict management. This study used data analysis techniques from James Spradley, namely domain analysis, taxonomy analysis and componential analysis. After conducted the analysis, dysfunctional conflict is more dominant than functional conflict. In addition, avoiding becomes a conflict management that is widely used by the main character in managed the conflict. The Elemental movie has depicted the existence of functional and dysfunctional conflicts.